Calcium Paradox, Vitamin D and Vitamin K2 - Mose, Johanes C. (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2024)
Calsium supplementation during pregnancy is a routine standard practice for antenatal care recommended by WHO, FIGO, POGI as well as Indonesia Ministry of Health. Calcium is one of essential micronutrients needed in human life, especially during pregnancy known for bone and teeth development, prevent osteoporosis, involved in blood coagulation, prevent haemorrhages during pregnancy and post partum periods, muscle contraction, prevent hypertension, preeclampsia, prematurity, IUGR, LBW, stunting, increase immunity, etc.Prevalence of hypocalcemia varies from 60 % to 70.5 % in low-medium income countries (LMIC) and 30 % to 60 % in high income countries (HIC).A systematic review study conducted in 2019 reported a prevalence of low calcium consumption less than 800 mg/day (normal consumption is around 1000-1200 mg/day) was 29 % in HIC and 82 % in LMIC, including Malaysia 377 mg/day and Indonesia < 400 mg/day.Calcium metabolism in human body is very much depend on the normal level of vitamin D, magnesium and parathyroid hormone in blood. Vitamin D is mainly needed for the absorption of calcium in intestine. The combination of vitamin D and calcium supplementation is very much recommended.